Computational Study of Oxidized Linoleic Acid on Dipeptidyl Peptidase-4 Shedding - Suhargo, Listijani; Sumitro, Sutiman B.; Widodo, Nashi (Proceeding International Conference on Global Resource Conservation, 2015)
Dipeptidyl Peptidase-4 is a epithelial transmembrane protein of many cell type such as gastrointestinal tract, biliary tract, pancreas, kidney, thymus, uterus, prostate and capillary endothelial cell. It has a cytoplasmic domain (amino acids 1-6), transmembrane domainÂ (amino acid 7-28) and extracellular domain (amino acids 29-766). Dipeptidyl Peptidase-4 also found in soluble form of serum and other body fluid. Soluble DPP-4 has not a cytoplasmic domain and transmembrane domain. The level of soluble dipeptidyl peptidase-4 increased in diabetes. In diabetes, Hydrogen Peroxide as Reactive Oxygen Species (ROS) involved in transmembrane DPP-4 shedding to produce soluble DPP-4. Hydrogen peroxide can be converted into hydroxyl radicals (â¢OH) which are highly reactive. Hydroxyl radicals can oxidizeÂ fatty acid such as linoleic acid which is found mainly in Low Density Lipoprotein (LDL). This study was aimed to elucidate the molecular mechanism of oxidation to shedÂ transmembrane DPP-4 to produce soluble DPP-4. The DPP-4 model used is DPP-4 with 10-766 amino acid derived from Uniprot and 3D Jigsaw program. Oxidized linoleic acids were derived from NCBI pubchem. DPP-4 as a receptor was docked with oxidized linoleic acids as ligand by patchdock program. And the result show that 13-HODE more easily interact acid with DPP-4thanÂ the other oxidized linoleic. ThatÂ oxidants had the active site on DPP-4 (Threonine 36 and Alanine 37) that allow the shedding of transmembrane DPP-4 to produce soluble DPP-4. But that oxidant also interact with the otherÂ siteÂ of DPP-4 that may destroy the catalytic domain.Keywords: DPP-4; oxidized linoleic acid; shedding